Acting Women: Gender Roles in Ana Istarú’s Hombres en escabeche, Elena Garro’s La señora en su balcón, and Carmen Boullosa’s Cocinar hombres - Miller, Elaine M. (Latin American Theatre Review, 2010)
Ana Istarú’s Hombres en escabeche (2000) combines humor and serious commentaryto break down the binary division of gender roles in Costa Rican society. This essay exploreskey commonalities in this play and Mexican playwrights Elena Garro’s La señora en su balcón(1963) and Carmen Boullosa’s Cocinar hombres (1987). The three plays develop metaphorsinvolving food to express the confining roles traditionally assigned to women and to eventuallytransform them into acts of creative independence. Although the decisive actions taken bythe female protagonists, who are conscious of the performative nature of gender and refuse toplay the roles assigned to them by patriarchal culture, and their approach to calling for socialchanges vary, all of these plays conclude with their empowerment. (EMM, Article in English)